2013
DOI: 10.1097/pts.0b013e31827cdc3b
|View full text |Cite
|
Sign up to set email alerts
|

Description and Evaluation of Adaptations to the Global Trigger Tool to Enhance Value to Adverse Event Reduction Efforts

Abstract: The GTT can be adapted to health-care organizations' goals and resource limitations. This flexibility was essential in crossing our organization's "value threshold."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 16 publications
2
62
0
Order By: Relevance
“…34 The GTT consists of 47-55 triggers to identify potential AEs. Reviewing the preventability of adverse events is originally no part of the GTT method, but has been recently included in the studies of Schildmeijer et al, 35 Kennerly et al, 36 Najjar et al 37 and Hwang et al 38 In contrast, the HMPS consists of 16-18 screening criteria (triggers), 27 leading questions for AE detection, of which three questions are crucial for AE determination: injury present; resulting in prolongation of hospital stay, temporary or permanent disability or death and caused by healthcare management. Determination of preventability of AEs is standard within the HMPS method.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…34 The GTT consists of 47-55 triggers to identify potential AEs. Reviewing the preventability of adverse events is originally no part of the GTT method, but has been recently included in the studies of Schildmeijer et al, 35 Kennerly et al, 36 Najjar et al 37 and Hwang et al 38 In contrast, the HMPS consists of 16-18 screening criteria (triggers), 27 leading questions for AE detection, of which three questions are crucial for AE determination: injury present; resulting in prolongation of hospital stay, temporary or permanent disability or death and caused by healthcare management. Determination of preventability of AEs is standard within the HMPS method.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Local involvement helps tailor the tool to local conditions, is a powerful driving force for introducing changes to practice and, if involvement is multidisciplinary, then iatrogenic occurrences right along the patient's care pathway can be assessed [39]. In addition, providing feedback to tool designers opens a door to dialogue on risk management.…”
Section: Discussionmentioning
confidence: 99%
“…Landrigan et al 11 reported that internal reviewers rated 63.1% of the AEs found as preventable. Kennerly et al 15 reported that among hospital-acquired AEs, 12.5% were judged to be preventable or probably preventable, and an additional 59% were possibly preventable. In a newly published study, as much as 87% of AEs present on admission to hospital were considered ‘preventable/possibly preventable’ 16…”
Section: Discussionmentioning
confidence: 99%